Cancer incidence among semiconductor and electronic storage device workers. Issue 1 (17th July 2006) - Bender, T J; Beall, C; Cheng, H; Herrick, R F; Kahn, A R; Matthews, R; Sathiakumar, N; Schymura, M J; Stewart, J H; Delzell, E
Abstract : Aims: To evaluate cancer incidence among workers at two facilities in the USA that made semiconductors and electronic storage devices. Methods: 89 054 men and women employed by International Business Machines (IBM) were included in the study. We compared employees' incidence rates with general population rates and examined incidence patterns by facility, duration of employment, time since first employment, manufacturing era, potential for exposure to workplace environments other than offices and work activity. Results: For employees at the semiconductor manufacturing facility, the standardised incidence ratio (SIR) for all cancers combined was 81 (1541 observed cases, 95% confidence interval (CI) 77 to 85) and for those at the storage device manufacturing facility the SIR was 87 (1319 observed cases, 95% CI 82 to 92). The subgroups of employees with ≥15 years since hiring and ≥5 years worked had 6–16% fewer total incidents than expected. SIRs were increased for several cancers in certain employee subgroups, but analyses of incidence patterns by potential exposure and by years spent and time since starting in specific work activities did not clearly indicate that the excesses were due to occupational exposure. Conclusions: This study did not provide strong or consistent evidence of causal associations with employment factors. Data on employees with long potential induction time and many years worked were limited. Further follow-up will allow a more informative analysis of cancer incidence that might be plausibly related to workplace exposures in the cohort.